Derivation of Breast Cancer Cell Lines Under Physiological (5%) Oxygen Concentrations - Euphemia Y. Leung; Euphemia Y. Leung; Marjan E. Askarian-Amiri; Marjan E. Askarian-Amiri; Dean C. Singleton; Carole Ferraro-Peyret; Carole Ferraro-Peyret; Wayne R. Joseph; Graeme J. Finlay; Graeme J. Finlay; Reuben J. Broom; Purvi M. Kakadia; et al. (Frontiers in Oncology, 2018)
Background: Most human breast cancer cell lines currently in use were developed and are cultured under ambient (21%) oxygen conditions. While this is convenient in practical terms, higher ambient oxygen could increase oxygen radical production, potentially modulating signaling pathways. We have derived and grown a series of four human breast cancer cell lines under 5% oxygen, and have compared their properties to those of established breast cancer lines growing under ambient oxygen.Methods: Cell lines were characterized in terms of appearance, cellular DNA content, mutation spectrum, hormone receptor status, pathway utilization and drug sensitivity.Results: Three of the four lines (NZBR1, NZBR2, and NZBR4) were triple negative (ER-, PR-, HER2-), with NZBR1 also over-expressing EGFR. NZBR3 was HER2+ and ER+ and also over-expressed EGFR. Cell lines grown in 5% oxygen showed increased expression of the hypoxia-inducible factor 1 (HIF-1) target gene carbonic anhydrase 9 (CA9) and decreased levels of ROS. As determined by protein phosphorylation, NZBR1 showed low AKT pathway utilization while NZBR2 and NZBR4 showed low p70S6K and rpS6 pathway utilization. The lines were characterized for sensitivity to 7-hydroxytamoxifen, doxorubicin, paclitaxel, the PI3K inhibitor BEZ235 and the HER inhibitors lapatinib, afatinib, dacomitinib, and ARRY-380. In some cases they were compared to established breast cancer lines. Of particular note was the high sensitivity of NZBR3 to HER inhibitors. The spectrum of mutations in the NZBR lines was generally similar to that found in commonly used breast cancer cell lines but TP53 mutations were absent and mutations in EVI2B, LRP1B, and PMS2, which have not been reported in other breast cancer lines, were detected. The results suggest that the properties of cell lines developed under low oxygen conditions (5% O2) are similar to those of commonly used breast cancer cell lines. Although reduced ROS production and increased HIF-1 activity under 5% oxygen can potentially influence experimental outcomes, no difference in sensitivity to estrogen or doxorubicin was observed between cell lines cultured in 5 vs. 21% oxygen.